2022
DOI: 10.1021/acs.organomet.2c00202
|View full text |Cite
|
Sign up to set email alerts
|

Direct Benzene Hydroxylation with Dioxygen Induced by Copper Complexes: Uncovering the Active Species by DFT Calculations

Abstract: The direct oxidation of benzene into phenol using molecular oxygen at very mild temperatures can be promoted in the presence of the copper complex Tp Br3 Cu(NCMe) in the homogeneous phase in the presence of ascorbic acid as the source of protons and electrons. The stoichiometric nature, relative to copper, of this transformation prompted a thorough DFT study in order to understand the reaction pathway. As a result, the dinuclear species Tp Br3 Cu II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This unreactivity of qnt 20 toward the oxidation of benzene could be attributed to the lack of oxyl character of the oxygen atom. In the copper complex studied by Lledós et al, the oxygen atom possesses a spin density of 1.18 e/Å 3 , 63 whereas this value for the analogous oxygen in qnt 20 is only 0.094 e/Å 3 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This unreactivity of qnt 20 toward the oxidation of benzene could be attributed to the lack of oxyl character of the oxygen atom. In the copper complex studied by Lledós et al, the oxygen atom possesses a spin density of 1.18 e/Å 3 , 63 whereas this value for the analogous oxygen in qnt 20 is only 0.094 e/Å 3 .…”
Section: Resultsmentioning
confidence: 93%
“…Lledós and co-workers recently computationally demonstrated that a Cu II (μ–O • )(μ–OH)Cu II complex is capable of oxidizing benzene into phenol in a stoichiometric reaction via the oxygen-rebound mechanism as well as a σ-complex mechanism ( Scheme 2 a). 63 The σ-complex mechanism begins with the attack of an oxyl species on the π system of benzene, leading to the formation of a σ complex. In a subsequent step, a proton shuttle facilitates the transfer of a proton from the ipso carbon to the oxygen, producing phenol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Examples of triplet-triplet energy transfer using water as solvent are rare and not well established in organic synthesis. [15] Micelles have been presented as suitable nanoreactors for carrying out a wide range of reactions, [16] particularly transitionmetal-catalysed [17] or cascade type [18] reactions. The array of disclosed works on micellar catalysis demonstrates that micelles not only offer solubility in water, as a more benign solvent, [19] but might also offer additional advantages which are unique and tuneable by careful selection of the employed catalysts, reactants [20] and amphiphiles.…”
Section: Introductionmentioning
confidence: 99%